AIAA Scitech 2019 Forum 2019
DOI: 10.2514/6.2019-1355
|View full text |Cite
|
Sign up to set email alerts
|

Aeroelastic eigenvalue analysis of a variable speed rotor blade with an applied compressive load

Abstract: Variable speed rotors are one possible way to meet the industry's increasing demands on noise emissions, flight envelopes and power requirements. The use of this technology is largely prohibited due to the presence of dynamic interactions at various rotor speeds that would lead to excessive vibratory loads. One concept being considered to overcome this is modal tuning by means of an applied compressive load. Herein, the impact of the combined effects of compressive loading, aerodynamic loading in hover and red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…The use of a tendon as the tunable vibration absorber in the helicopter tail boom was studied in [23] while the longitudinal tensile loads were proposed as a means for resonance avoidance in the spinning shafts operating at the supercritical speeds [24]. The idea to incorporate a tendon in the rotorcraft blade to introduce a means of controlling its dynamics was originally proposed in [25]. Since then, it was shown that the blade-tendon system with a free tendon can be used as a means of resonance avoidance [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The use of a tendon as the tunable vibration absorber in the helicopter tail boom was studied in [23] while the longitudinal tensile loads were proposed as a means for resonance avoidance in the spinning shafts operating at the supercritical speeds [24]. The idea to incorporate a tendon in the rotorcraft blade to introduce a means of controlling its dynamics was originally proposed in [25]. Since then, it was shown that the blade-tendon system with a free tendon can be used as a means of resonance avoidance [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The present paper was motivated by the future application of an active tendon concept in rotorcraft as investigated within the SABRE project [1,3]. It was already shown [2,38] that the axial force alone has potential to allow rotorcraft to operate with variable rotor speed. This paper indicates that the tendon can be used to induce this axial force which consequently reduces the natural frequencies of the blade.…”
Section: Discussionmentioning
confidence: 99%
“…For the axial force applied through the elastic axis, and neglecting the effect of warping and the cross-sectional parameter β y , Eqs. (1a)-(1c) augmented by the effect of centrifugal forces and beam pre-twist were used in [28,29] to demonstrate a possibility of using the axial force for resonance avoidance in rotorcraft. The full set of EoM in Eq.…”
Section: Equations Of Motion and Boundary Conditionsmentioning
confidence: 99%
“…The underlined terms in these two equations capture the contribution of tendon-induced forces in the shear directions. These terms are invariant to the position of the tendon (they do not depend on e y or e z ) and were also used in [21,22,26,27] for the beam-tendon systems and approximated in [28,29] for a compressively loaded blade. Equations (3b) and (3d) represent the bending moments acting on the beam.…”
Section: Equations Of Motion and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation